NiTi-layered double hydroxide nanosheets toward high-efficiency flame retardancy and smoke suppression for silicone foam. (October 2022) - Zhou, Lin-Lin; Li, Wen-Xiong; Zhao, Hai-Bo; Wang, Jun-Sheng; Zhao, Bin
Highlights: Novel NiTi-LDH nanosheet was designed as an effective flame-retardant and smoke-suppressor. NiTi-LDH nanosheet possessed an average thickness of 1.93 ± 0.02 nm and large specific surface areas. 1 phr NiTi-LDH endowed silicone foam with outstanding flame retardancy and smoke suppression. Highly efficient flame retardant silicone foam without halogen and phosphorus. Abstract: There is a need for further enhancing fire safety of silicone foam (SiF) due to its popularization and application in aircraft and the latest generation of high-speed train. We prepared a novel NiTi-layered double hydroxide nanosheets (NiTi-LDH) by a co-precipitation method, which was used as highly effective flame-retardant and smoke-suppressor for SiF. FTIR and X-ray photoelectron spectrometerwere conducted to analyze the chemical structure of NiTi-LDH. The microstructure and crystal phase of NiTi-LDH were determined by scanning electron microscope (SEM), X-ray diffraction (XRD), and transmission electron microscopy. The results of atomic force microscope and Brunauer-Emmett-Teller analyses demonstrated that NiTi-LDH possessed an ultra-thin structure with an average thickness of 1.93 ± 0.02 nm and large specific surface areas (194.4 m 2 g −1 ). After being evaluated by vertical flame testing (UL-94), limiting oxygen index (LOI), and cone calorimeter test, only 1.0 phr NiTi-LDH made SiF pass UL-94 V-0 rating with an increased LOI (28.7–30.3%), and greatly inhibited smoke release compared to untreated silicone foam. Meanwhile, both the maximum smoke density and smoke density rank of SiF/NiTi-LDH-1.0 are lower than those of SiF. To further understand the flame retardant action of NiTi-LDH, we used thermogravimetric analysis (TGA), XRD and FTIR to investigate its thermal decomposition behavior, the evolutions of chemical/crastal structures during heating. X-ray energy dispersive spectroscopy coupled with SEM (SEM-EDS) and TGA-FTIR were adopted to analyze the char residue and gaseous products. NiTi-LDH exhibited possible catalytic actions for high efficiency smoke suppression and flame retardancy based on char-forming and flammable volatiles inhibition in both the condensed and gaseous phase.